Reproduction of the FC/DFC units in nucleoli - Smirnov, Evgeny; Hornáček, Matúš; Kováčik, Lubomír; Mazel, Tomáš; Schröfel, Adam; Svidenská, Silvie; Skalníková, Magdalena; Bartová, Eva; Cmarko, Dušan; Raška, Ivan (Nucleus (Austin, Tex.), 2016)
The essential structural components of the nucleoli, Fibrillar Centers (FC) and Dense Fibrillar Components (DFC), together compose FC/DFC units, loci of rDNA transcription and early RNA processing. In the present study we followed cell cycle related changes of these units in 2 human sarcoma derived cell lines with stable expression of RFP-PCNA (the sliding clamp protein) and GFP-RPA43 (a subunit of RNA polymerase I, pol I) or GFP-fibrillarin. Correlative light and electron microscopy analysis showed that the pol I and fibrillarin positive nucleolar beads correspond to individual FC/DFC units. In vivo observations showed that at early S phase, when transcriptionally active ribosomal genes were replicated, the number of the units in each cell increased by 60-80%. During that period the units transiently lost pol I, but not fibrillarin. Then, until the end of interphase, number of the units did not change, and their duplication was completed only after the cell division, by mid G1 phase. This peculiar mode of reproduction suggests that a considerable subset of ribosomal genes remain transcriptionally silent from mid S phase to mitosis, but become again active in the postmitotic daughter cells.
Keywords: HeLa Cells; Cell Nucleolus; replication; lidé; HeLa buňky; S fáze; S Phase; FC/DFC units; rDNA; nucleolus; buněčné jadérko; cell cycle; Humans